2022
DOI: 10.1136/bmjpo-2021-001349
|View full text |Cite
|
Sign up to set email alerts
|

Use of melatonin: a single-centre audit

Abstract: Sleep disorders in childhood are common. Melatonin is prescribed by UK community paediatricians to treat sleep disorders, but practice is not standardised. This audit reviewed melatonin prescribing within a community paediatric department in a 12-month period. 682 children received melatonin prescriptions; a random sample of 198 records were reviewed. The most common underlying condition was autism spectrum disorder (ASD) in 28%. 41% had no underlying diagnosis when melatonin was initiated and were waiting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…One small, randomized study demonstrated statistically significant improvements in sleep parameters with melatonin 5 mg compared with placebo in children 6–12 years of age [ 25 ]. Short term use of melatonin has demonstrated good safety [ 13 ], but several register-based studies show that long-term use is common [ 6 , 12 ]. Considering the multiple physiological effects of melatonin and the scarce knowledge of long-term safety in the pediatric population [ 13 , 26 , 27 ], along with an exponential rise in use, it is of great importance for health care professionals, care givers and regulatory authorities to follow up the use of melatonin in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One small, randomized study demonstrated statistically significant improvements in sleep parameters with melatonin 5 mg compared with placebo in children 6–12 years of age [ 25 ]. Short term use of melatonin has demonstrated good safety [ 13 ], but several register-based studies show that long-term use is common [ 6 , 12 ]. Considering the multiple physiological effects of melatonin and the scarce knowledge of long-term safety in the pediatric population [ 13 , 26 , 27 ], along with an exponential rise in use, it is of great importance for health care professionals, care givers and regulatory authorities to follow up the use of melatonin in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is used for sleep disorders in children and adolescents, and it is recommended in national guidelines as a second line of treatment after non-pharmacological alternatives [ 9 , 10 ]. Although melatonin is recommended as a short-term treatment, several register-based studies show that long-term use is common [ 6 , 8 , 11 , 12 ]. These findings indicate a substantial exposure for some individuals where treatment is initiated during childhood and continues long-term.…”
Section: Introductionmentioning
confidence: 99%
“…The prescription of aMT, most particularly to pediatric patients, has experienced nearly a tenfold increase in several European countries in an 11-year period [41,44]. This, together with the lack of specific guidelines on aMT dosage in children with neurodevelopmental disorders and the scarcity of double-blind randomized placebo-controlled trials [45], has raised concerns about the potential current misuse of aMT and the long-term adverse effects derived from this hormone [46,47]. Although the administration of aMT to children has traditionally been considered safe [36], it is worth noticing a lack of consistency between studies in the approaches taken to measure adverse events in patients with neurological disabilities [48].…”
Section: Introductionmentioning
confidence: 99%